The Role of Self-Concept in Modulating the Effectiveness of Nature-Based Science Instruction - Jatmiko, A.; Asyhari, A.; Irwandani, I.; Soeharto, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This study investigates the intersection between academic self-concept and the efficacy of Nature-Based Science Instruction (NBSI) in shaping the educational experiences of future science teachers. A mixed-methods design, encompassing the Academic Self-Concept Questionnaire and Nature-Based Science Instruction Assessment, enabled a comprehensive exploration of this dynamic. The research found that self-efficacy and self-competence, key components of self-concept, significantly determine the success of NBSI. These elements shape and are shaped by the learning environment, with reflective practices within NBSI notably enhancing academic self-concept and learning outcomes. The study's conclusions provide new insights into educational psychology, emphasizing the necessity of incorporating psychological factors into science curriculum development for more effective pedagogical strategies.